2014
DOI: 10.1007/s12010-014-1431-z
|View full text |Cite
|
Sign up to set email alerts
|

Alginate as a Cell Culture Substrate for Growth and Differentiation of Human Retinal Pigment Epithelial Cells

Abstract: The purpose of this study was to evaluate retinal pigment epithelium (RPE) cells' behavior in alginate beads that establish 3D environment for cellular growth and mimic extracellular matrix versus the conventional 2D monolayer culture. RPE cells were encapsulated in alginate beads by dripping alginate cell suspension into CaCl2 solution. Beads were suspended in three different media including Dulbecco's modified Eagle's medium (DMEM)/F12 alone, DMEM/F12 supplemented with 10 % fetal bovine serum (FBS), and DMEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In a study, a thin film of purified alginate was used to demonstrate its ability to support the growth of RPE cells and their high proliferative rates [84]. In another study, alginate beads were used to demonstrate RPE cell sustenance and proliferation [85]. An arginine-glycine-aspartic-alginate (RGD-alginate) scaffold demonstrated feasibility for cell derivation and transplantation of RPE and neural retina [86].…”
Section: Biomaterials and Scaffolds Used For Tissue Engineering 41 Natural Biomaterials Used As Scaffoldsmentioning
confidence: 99%
“…In a study, a thin film of purified alginate was used to demonstrate its ability to support the growth of RPE cells and their high proliferative rates [84]. In another study, alginate beads were used to demonstrate RPE cell sustenance and proliferation [85]. An arginine-glycine-aspartic-alginate (RGD-alginate) scaffold demonstrated feasibility for cell derivation and transplantation of RPE and neural retina [86].…”
Section: Biomaterials and Scaffolds Used For Tissue Engineering 41 Natural Biomaterials Used As Scaffoldsmentioning
confidence: 99%
“…In a study, thin film of purified alginate was used to demonstrate its ability to support the growth of RPE cells and their high proliferative rates [84]. In another study, alginate beads were used to demonstrate RPE cell sustenance and proliferation [85]. An arginine-glycine-aspartic-alginate (RGD-alginate) scaffold demonstrated feasibility for cell derivation and transplantation of RPE and neural retina [86].…”
Section: Natural Biomaterials Used As Scaffoldsmentioning
confidence: 99%
“…Heidari et al evaluated the behavior of human RPE cells on alginate beads as a cell culture substrate and showed that RPE cells could grow and proliferate on alginate beads in vitro. However, consecutive passages of cells caused the cells to lose their pigments [73]. Hunt et al further demonstrated the potential of RGD-alginate scaffolds for the derivation, transport, and transplantation of neural retina and RPE [44].…”
Section: Scaffold Biocompatibilitymentioning
confidence: 99%